Nanostructured polyethylene reactor blends with tailored trimodal molar mass distributions as melt-processable all-polymer composites - Stürzel, Markus Roland; Enders, Markus (Macromolecules, 2016)
Tailoring trimodal polyethylene (PE) molar mass distributions by means of ethylene polymerization on three-site catalysts, supported on functionalized graphene (FG), enables nanophase separation during polymerization and melt processing, paralleled by PE self-reinforcement. Typically, FG/MAO-supported three-site catalysts combine bis(iminopyridyl)chromium trichloride (CrBIP), producing PE wax having high crystallization rate, and quinolylcyclopentadienylchromium dichloride (CrQCp), forming in situ ultrahigh molecular weight PE (UHMWPE) nanostructures, with bis(iminopyridyl)iron dichloride (FeBIP) or bis(tert-butyl cyclopentadienyl)zirconium (ZrCp), respectively, producing HDPE with variable intermediate molar mass. During injection molding, the formation of shish-kebab fiber-like extended-chain UHMWPE structures, as verified by SEM, AFM, and DSC, account for effective self-reinforcement. Only in the presence of high UHMWPE content, PE wax, usually an unwanted byproduct in HDPE synthesis, functions as a built-in processing aid and enables the incorporation of much higher UHMWPE contents (30 wt %) than previously thought to be tolerable in injection molding. Whereas the incorporation of UHMWPE/PE wax blends improves stiffness and strength, the simultaneous FG dispersion accounts for substantially higher impact strength.
Gesehen am 26.05.2020